Patient safety in primary health care: a systematic review - Simone Grativol Marchon; Walter Vieira Mendes Junior (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2014)
The aim of this study was to identify methodologies to evaluate incidents in primary health care, types of incidents, contributing factors, and solutions to make primary care safer. A systematic literature review was performed in the following databases: PubMed, Scopus, LILACS, SciELO, and Capes, from 2007 to 2012, in Portuguese, English, and Spanish. Thirty-three articles were selected: 26% on retrospective studies, 44% on prospective studies, including focus groups, questionnaires, and interviews, and 30% on cross-sectional studies. The most frequently used method was incident analysis from incident reporting systems (45%). The most frequent types of incidents in primary care were related to medication and diagnosis. The most relevant contributing factors were communication failures among member of the healthcare team. Research methods on patient safety in primary care are adequate and replicable, and they will likely be used more widely, thereby providing better knowledge on safety in this setting.